2022
DOI: 10.1371/journal.pone.0272362
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, anti-proliferative evaluation, docking, and MD simulations studies of new thiazolidine-2,4-diones targeting VEGFR-2 and apoptosis pathway

Abstract: We report herein, the design and synthesis of thiazolidine-2,4-diones derivatives as new inhibitors for VEGFR-2. The designed members were assessed for their in vitro anticancer activity against four cancer cell lines; A549, Caco-2, HepG-2 and MDA-MB-231. Compound 14a showed the most potent effects against Caco-2, and HepG-2 cell lines (IC50 = of 1.5 and 31.5 μM, respectively). Next, the in vitro VEGFR-2 inhibitory activity, safety profiles and selectivity indices were examined for all the synthesized members … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 72 publications
1
18
0
Order By: Relevance
“…Frontiers in Chemistry frontiersin.org polymerization inhibitor (Dwivedi et al, 2022), PARP-1 inhibitor 2 (Syam et al, 2022), CDK2 inhibitor 3 (Qayed et al, 2022), HDAC-1-3 inhibitor 4 (Cheshmazar et al, 2022), VEGFR-2 inhibitor 5 (Taghour et al, 2022) were identified for cancer therapies. Furthermore, AChE inhibitor 6 (Macedo Vaz et al, 2022) for treatment of Alzheimer's disease and Mtb RNAP inhibitor 7 (Mekonnen Sanka et al, 2022) for antitubercular and antimicrobial treatment were deserve further study.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Frontiers in Chemistry frontiersin.org polymerization inhibitor (Dwivedi et al, 2022), PARP-1 inhibitor 2 (Syam et al, 2022), CDK2 inhibitor 3 (Qayed et al, 2022), HDAC-1-3 inhibitor 4 (Cheshmazar et al, 2022), VEGFR-2 inhibitor 5 (Taghour et al, 2022) were identified for cancer therapies. Furthermore, AChE inhibitor 6 (Macedo Vaz et al, 2022) for treatment of Alzheimer's disease and Mtb RNAP inhibitor 7 (Mekonnen Sanka et al, 2022) for antitubercular and antimicrobial treatment were deserve further study.…”
Section: Figurementioning
confidence: 99%
“…To effectively and efficiently design and develop new drugs, computational methods had been applied for drug design including target identification, seeking out and optimizing lead compounds prediction of pharmacokinetic and toxicological properties as well as compound synthesis by molecular docking and molecular dynamics, virtual screening, pharmacophore and ADMET prediction. Novel quinazoline derivative 1 as tubulin polymerization inhibitor ( Dwivedi et al, 2022 ), PARP-1 inhibitor 2 ( Syam et al, 2022 ), CDK2 inhibitor 3 ( Qayed et al, 2022 ), HDAC-1-3 inhibitor 4 ( Cheshmazar et al, 2022 ), VEGFR-2 inhibitor 5 ( Taghour et al, 2022 ) were identified for cancer therapies. Furthermore, AChE inhibitor 6 ( Macedo Vaz et al, 2022 ) for treatment of Alzheimer’s disease and Mtb RNAP inhibitor 7 ( Mekonnen Sanka et al, 2022 ) for antitubercular and antimicrobial treatment were deserve further study.…”
Section: Computational Chemistry In Drug Discoverymentioning
confidence: 99%
“…In silico studies are preferred for a variety of reasons, including the restrictions on cost, time, and effort as well as the strict laws regarding animal testing. 25,26 Although there are many in vitro studies that can be carried out to investigate the properties of ADMET, they are not always the most effective method. 27,28 Therefore, the ADMET characteristics of the examined compounds were assessed computationally using Discovery Studio 4.0.…”
Section: 23mentioning
confidence: 99%
“…Various chemotherapeutic agents have been commonly and successfully used for the treatment of cancer [ 1 , 2 , 3 ]; however, the development of inducible drug resistance and the difficulty to limit the associated side effects are often the main cause of chemotherapy failure. Therefore, the identification of novel anticancer drugs with great cancer-selective toxicity remains the main challenge for medicinal chemistry researchers [ 4 , 5 , 6 , 7 ]. The flavone scaffold has emerged as a versatile source in the field of drug discovery ( Figure 1 A).…”
Section: Introductionmentioning
confidence: 99%